A novel secondary ALK gene mutation which resistant to second-generation TKIs: a case report and literature review - Cheng, Xiaqin; Liu, Jia; Hu, Qiongxia; Gao, Yingchun; Zhou, Lin (Frontiers in Oncology, 2024)
Background: Adenocarcinoma with positive echinoderm microtubule-associated protein-like 4 gene and anaplastic lymphoma kinase (EML4-ALK) gene fusion accounts for 3-7% of lung cancer cases and can be targeted with ALK tyrosine kinase inhibitors (TKIs). Second-generation TKIs are the standard of care for targeted populations, especially those with central nervous system (CNS) metastasis. However, most patients eventually experience disease progression because of drug resistance caused by multiple mechanisms, predominantly secondary mutations. Case description: We present a female advanced non-small cell lung cancer (NSCLC) case with positive EML4-ALK gene fusion, in which disease progression occurred in only 3 months after first-line treatment with alectinib. Two secondary mutations were detected by next-generation sequencing; one was V1180L located in exon 23, and the other was E803Q located in exon 14, which was a novel mutation that had never been reported. Ensartinib and ceritinib were administered as second-line and third-line treatments. However, the response to these TKIs was poor, and her overall survival was only 7 months. Conclusion: The secondary mutation E803Q located in exon 14 seems resistant to most second-generation ALK-TKIs. If there is an opportunity, the efficacy of the third-generation ALK-TKI loratinib should be tested.